Heart of the Story: Connecting Digital Storytelling to Sociology of Emotions - Kabakcı Gökçe Zeybek (Cultural Science)
This paper is based upon a paper delivered at the ‘Create, Act, Change’: The 5th International Digital Storytelling Conference in May 2013, in Ankara, Turkey http://www.digitalstorytelling2013.hacettepe.edu.tr/documents/program_web.pdf. It aims to put forward a connection between digital storytelling and the sociology of emotions. For this purpose, it briefly gives a picture of the field of sociology of emotions. The paper sets out to offer some self-reflection, because the aim of this piece is closely related to the academic interests of the writer. Following the path of self-reflection, it introduces common points between digital storytelling and the sociology of emotions.